Implementation of an Internal Quality Assurance System (IQAS) in Vocational Schools - Siti Miftakhul Jannah; Karwanto Karwanto; Umi Anugerah Izzati (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to understand and analyze content related to implementing an internal quality assurance system based on eight national education standards in Vocational High Schools (VHS) with CIPP model evaluation metrics. The evaluation was conducted to see the results of implementing the internal quality assurance system in vocational schools by eight national education standards. Methods: The type of research used is evaluation research. In this research, researchers used quantitative methods with the CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam. The population in this research is the academic community of VHS Sunan Giri Menganti Gresik, which knows and understands the implementation of the internal quality assurance system (IQAS). Based on existing data, the population in this study was 72 people, including the school principal, curriculum leader, teacher council, education staff, and head of the school quality assurance team. Result: IQAS provides services by eight National Education Standards (SNP) to exceed the expectations of educational service users. School Self-Evaluation (EDS) describes the quality and produced information processed using government information systems. This mutual mapping is explained to identify areas of improvement using the IQAS Vocational School Transformation guide. Novelty: Implementing the quality assurance system in model schools and its impact is carried out through four stages: Setting Standards, Fulfilling Standards, Continuous Evaluation, and Quality Improvement. Decentralization of education encourages school autonomy to improve the quality of institutions and their graduates with strategies such as school reviews, benchmarking, quality assurance, and quality control.